Blood–testis barrier and Sertoli cell function: lessons from SCCx43KO mice. Issue 2 (February 2016) - Gerber, Jonathan; Heinrich, Julia; Brehm, Ralph
Abstract : The gap junction protein connexin43 (CX43) plays a vital role in mammalian spermatogenesis by allowing for direct cytoplasmic communication between neighbouring testicular cells. In addition, different publications suggest that CX43 in Sertoli cells (SC) might be important for blood–testis barrier (BTB) formation and BTB homeostasis. Thus, through the use of the Cre-LoxP recombination system, a transgenic mouse line was developed in which only SC are deficient of the gap junction protein, alpha 1 ( Gja1 ) gene. G ja1 codes for the protein CX43. This transgenic mouse line has been commonly defined as the SC specific CX43 knockout (SCCx43KO) mouse line. Within the seminiferous tubule, SC aid in spermatogenesis by nurturing germ cells and help them to proliferate and mature. Owing to the absence of CX43 within the SC, homozygous KO mice are infertile, have reduced testis size, and mainly exhibit spermatogenesis arrest at the level of spermatogonia, seminiferous tubules containing only SC (SC-only syndrome) and intratubular SC-clusters. Although the SC specific KO of CX43 does not seem to have an adverse effect on BTB integrity, CX43 influences BTB composition as the expression pattern of different BTB proteins (like OCCLUDIN, β-CATENIN, N-CADHERIN, and CLAUDIN11) is altered in mutant males. The supposed roles of CX43 in dynamic BTB regulation, BTB assembly and/or disassembly and its possible interaction with other junctional proteins composing this unique barrier are discussed. Data collectively indicate that CX43 might represent an important regulator of dynamic BTB formation, composition and function.